STARTEGI KEMENANGAN PARTAI AMANAT NASIONAL PADA PEMILU LEGISLATIF TAHUN 2019 DI KABUPATEN KEPULAUAN MERANTI - Nur Khomisah; M. Y. Tiyas Tinov (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
Legislative elections are an opportunity for political parties to compete and support candidates for legislative members who will sit in representative institutions or better known as the Regional People's Representative Council (DPRD). Political parties along with members of legislative candidates prepare strategies to win and gain legislative seats. Partai Amanat Nasional is one of the political parties that is highly considered in Meranti Islands Regency, because the Partai Amanat Nasional is a party that consecutively emerged as the winning party in the 2014-2019 and 2019-2024 legislative elections. Partai Amanat Nasional succeeded in obtaining the highest number of votes, namely 16,210 votes and obtaining 5 seats in the Regional People's Representative Council (DPRD).The purpose of this study is (1) Knowing the strategies used by the Partai Amanat Nasional in the 2019 legislative elections in Meranti Islands Regency, (2) Knowing the factors supporting the victory of the Partai Amanat Nasional in the 2019 legislative elections in Meranti Islands Regency, (3) Knowing the factors obstacles to the victory of the Partai Amanat Nasional in the 2019 legislative elections in Meranti Islands Regency.This research uses a qualitative approach. The research location is in the National Mandate Regional Leadership Council, Meranti Islands Regency. Data obtained by means of documentation and interviews. While the data analysis technique is descriptive qualitative analysis.The results of this study indicate that the Partai Amanat Nasional's strategy in the 2019 legislative elections in Meranti Islands Regency uses several strategies, namely the offensive strategy (attack) is carried out in several ways, namely the recruitment of legislative candidates, party campaigns, formation of successful teams, consolidation of votes, and approaches figure. Meanwhile, the Defense Strategy is carried out by maintaining public support and maintaining legislative candidates who have served. The factors that influenced the victory of the Partai Amanat Nasional were creating a network of cadres from the district level to the sub-district level, the Partai Amanat Nasional conducting a political campaign together with the proposed legislative candidates. The factor inhibiting the victory of the Partai Amanat Nasional was the lack of funds from both between Partai Amanat Nasional and legislative member candidates.Word key: Strategy, Partai Amanat Nasional, Legislative Election